2015
DOI: 10.4088/jcp.14m09228
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Psychotropic Medication in Patients With Emotionally Unstable Personality Disorder Under the Care of UK Mental Health Services

Abstract: Background:Guideline recommendations for the pharmacologic treatment of personality disorder lack consensus, particularly for emotionally unstable personality disorder (EUPD), and there is limited information on current prescribing practice in the United Kingdom.Objective: To characterize the nature and quality of current prescribing practice for personality disorder across the United Kingdom, as part of a quality improvement program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 21 publications
(26 reference statements)
6
61
0
Order By: Relevance
“…Data from a national audit of prescribing practice suggest that one-quarter of people who are in contact with mental health services are being prescribed a mood stabiliser. 72 Some patients report that prescribing medication during a crisis can help bring about short-term reductions in emotional distress. The results of the LABILE study support the clinical impression that prescribing lamotrigine can lead to improvements in mental health but suggest that this benefit is no greater than would be found if a placebo were to be prescribed.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Data from a national audit of prescribing practice suggest that one-quarter of people who are in contact with mental health services are being prescribed a mood stabiliser. 72 Some patients report that prescribing medication during a crisis can help bring about short-term reductions in emotional distress. The results of the LABILE study support the clinical impression that prescribing lamotrigine can lead to improvements in mental health but suggest that this benefit is no greater than would be found if a placebo were to be prescribed.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…77 Despite this, a recent national audit showed that 11% of women with BPD who are in contact with DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk secondary care mental health services are currently being prescribed this drug. 72 The data from the LABILE study showing the high level of unplanned pregnancies among women with BPD emphasise the importance of avoiding the use of unlicensed medications, such as sodium valproate, that are potentially teratogenic.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…What is important in the current study is that among those who had only the diagnosis of EUPD (n = 786), 28% were taking medications from 2 different medication classes, 23% from 3 classes, and 16% from 4 or more classes. 1 Unfortunately, this is not dissimilar to the 16-year data recently reported from the McLean Study of Adult Development. 9 After 16 years of prospective follow-up, 71% were still taking psychotropic medication, with 35.5% taking 3 or more concurrent medications, 18.6% taking 4 or more, and 6.9% taking 5 or more psychotropic medications.…”
Section: Current Knowledge On Effectiveness Of Medication In Bpdmentioning
confidence: 52%
“…he article by Paton and colleagues 1 on the use of psychotropic medication in patients with emotionally unstable personality disorder (EUPD) in the current issue of JCP is an important article. Making the assumption that EUPD as defined by ICD-10 (F60.3) is reasonably equivalent to borderline personality disorder (BPD) as defined in the United States by DSM, we are provided some insight into how practitioners think about prescribing medications to people with EUPD/BPD.…”
mentioning
confidence: 99%
“…7 The survey obtained data from clinics where the personality disorder is recognized (often as the primary diagnosis), but it did not examine clinical settings where personality disorder is either ignored or misdiagnosed. In contemporary practice, many personality disorder patients are given the diagnosis of bipolar disorder 8 and treated accordingly.…”
mentioning
confidence: 99%